Partial oxidation of alkanes by dioxiranes formed in situ at low temperature. (13th January 2018) - Yacob, Sara; Caulfield, Michael J.; Barckholtz, Timothy A.
Abstract : Partial oxidation catalysts capable of efficiently operating at low temperatures may limit the over-oxidation of alkane substrates and thereby improve selectivity. This work focuses on examining alkane oxidation using completely metal-free organocatalysts, dioxiranes. The dioxiranes employed here are synthesized by oxidation of a ketone using a terminal oxidant, such as hydrogen peroxide. Our work generates the dioxirane in situ, so that the process can be catalytic with respect to the ketone. To date, we have demonstrated selective partial oxidation of adamantane using ketone catalysts resulting in yields upwards of 60% towards 1-adamantanol with greater than 99% selectivity. Furthermore, we have demonstrated that changing the electrophilic character of the ketone R groups to contain more electron-donating ligands facilitates the dioxirane ring formation and improves overall oxidation yields. Isotopic labelling studies using H2 18 O2 show the preferential incorporation of an 18 O label into the parent ketone, providing evidence for a dioxirane intermediate formed in situ . The isotopic labelling studies, along with solvent effect studies, suggest the formation of peracetic acid as a reactive intermediate. This article is part of a discussion meeting issue 'Providing sustainable catalytic solutions for a rapidly changing world'.